A Colonial Affair Commerce, Conversion, and Scandal in French India - Agmon, Danna (Cornell University Press, 2017)
Danna Agmon's gripping microhistory is a vivid guide to the "Nayiniyappa Affair" in the French colony of Pondicherry, India. The surprising and shifting fates of Nayiniyappa and his family form the basis of this story of global mobilization, which is replete with merchants, missionaries, local brokers, government administrators, and even the French royal family. Agmon's compelling account draws readers into the social, economic, religious, and political interactions that defined the European colonial experience in India and elsewhere. Her portrayal of imperial sovereignty in France's colonies as it played out in the life of one beleaguered family allows readers to witness interactions between colonial officials and locals. Thanks to generous funding from Virginia Tech and its participation in TOME, the ebook editions of this book are available as Open Access volumes from Cornell Open (cornellpress.cornell.edu/cornell-open) and other repositories.